2021
DOI: 10.3389/fpsyg.2021.600076
|View full text |Cite
|
Sign up to set email alerts
|

Creative Lockdown? A Daily Diary Study of Creative Activity During Pandemics

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is influencing our lives in an enormous and unprecedented way. Here, we explore COVID-19-lockdown's consequences for creative activity. To this end, we relied on two extensive diary studies. The first, held on March 2019 (pre-pandemic), involved 78 students who reported their emotions and creativity over 2 weeks (927 observations). The second, conducted on March 2020 (during the pandemic and lockdown), involved 235 students who reported on their emotions, creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 61 publications
5
38
0
2
Order By: Relevance
“…This has included commonplace activities such as baking (Easterbrook-Smith, 2020) and watching films (Mikos, 2020), as well as new and emerging forms of artistic engagement such as singing in online choirs or from balconies (Taylor, 2020; see also www.musicacrossthebalconies.com) and visiting online art galleries (Shehadi, 2020). Creative and artistic activities have served a range of purposes during the COVID-19 pandemic in a variety of cultural contexts, such as health promotion, improving environmental aesthetics and memorializing (de-Graft Aikins, 2020), awareness-raising about the threats posed by the pandemic (Blanc et al, 2020), and emotion regulation (Karwowski et al, 2021). And, while musical activities can serve a range of purposes such as self-expression and social group bonding (Vanstone et al, 2016), musical activities have also facilitated emotion regulation during the pandemic (Martín et al, 2021;Steinberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This has included commonplace activities such as baking (Easterbrook-Smith, 2020) and watching films (Mikos, 2020), as well as new and emerging forms of artistic engagement such as singing in online choirs or from balconies (Taylor, 2020; see also www.musicacrossthebalconies.com) and visiting online art galleries (Shehadi, 2020). Creative and artistic activities have served a range of purposes during the COVID-19 pandemic in a variety of cultural contexts, such as health promotion, improving environmental aesthetics and memorializing (de-Graft Aikins, 2020), awareness-raising about the threats posed by the pandemic (Blanc et al, 2020), and emotion regulation (Karwowski et al, 2021). And, while musical activities can serve a range of purposes such as self-expression and social group bonding (Vanstone et al, 2016), musical activities have also facilitated emotion regulation during the pandemic (Martín et al, 2021;Steinberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some research has examined the influence of lockdown measures on creativity, finding that everyday creativity increased, particularly amongst those with a lower baseline of creative activity [28]. Among students, one study showed a slight increase in creative activity during the pandemic [29]. This study also showed that higher levels of creativity were associated with increased levels of reported positive affect.…”
Section: Introductionmentioning
confidence: 79%
“…The Crafts Council noted in its annual report the meditative benefits and increase in craft making during the pandemic [ 52 ]. Meanwhile, those with established psychiatric disorders, learning disabilities, neurodevelopmental conditions such as Autism Spectrum Disorder or ongoing treatment for conditions such as eating disorders experienced a severe reduction in access to points of statutory contact [ 53 , 54 , 55 ]. Services designed to implement salutogenic approaches in the community were reported to be overstretched during the pandemic, having been fragile and at capacity beforehand [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%